Screening and Profiling the Antioxidant Properties of Psychrophilic Microalgae and Cyanobacteria from the Baltic Sea - Vyacheslav F. Dolganyuk; Stanislav A. Sukhikh; Egor V. Kashirskih; Elena V. Ulrikh; Olga E. Kremleva; Olga O. Babich (Техника и технология пищевых производств)
At present, the issue of obtaining a complex of biologically active substances with antioxidant activity from psychrophilic Psychrophilic microalgae and cyanobacteria are a prospective source of biologically active antioxidant substances. New antioxidant complexes could expand the scope of their industrial application. The research objective was to identify psychrophilic microalgae and cyanobacteria from the Baltic Sea in order to study their antioxidant properties. The research featured psychrophilic microalgae and cyanobacteria obtained from the Curonian Lagoon and the Baltic Bay in the Baltic Sea, Kaliningrad Region, Russia, in March – May 2022. The authors used the Pasteur method and the flow cytometry method to isolate pure cultures of psychrophilic microalgae and cyanobacteria. The method of spectrophotometry made it possible to study the antioxidant activity by analyzing radical scavenging, reducing ability, and chelating. The psychrophilic microalga Skeletonema pseudocostatum demonstrated the highest antioxidant activity in all three methods: 17.62 μmol/g trolox equivalents according to the ABTS method, 58.16 μmol/g trolox equivalents according to the DPPH method, and 3.91 μmol/g trolox equivalents according to the FRAP method. The psychrophilic microalga Thalassiosira pseudonana exhibited the following values of antioxidant activity: 12.08, 12.42, and 3.13 μmol/g trolox equivalents, respectively. The antioxidant activity of the psychrophilic microalgae Fragilariopsis kerguelensis was 13.53, 11.84, and 1.09 μmol/g trolox equivalents, respectively. The antioxidant activity of the psychrophilic cyanobacterium Aphanizomenon gracile was 15.73, 19.89, and 2.47 μmol/g trolox equivalents, respectively. The antioxidant activity of the psychrophilic cyanobacterium Anabaena cylindrica was 12.62, 13.16, and 2.16 μmol/g trolox equivalents, respectively. The samples of psychrophilic microalgae and cyanobacteria obtained from natural environment in the Russian Baltic Sea demonstrated good antioxidant properties, which makes them a potential raw material for new pharmaceutical substances.